2008
DOI: 10.1080/15538600802501953
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Minority Bisexual Women: Understanding the Invisible Population

Abstract: Lesbian and gay identity development has received increased attention while bisexual identity has received limited consideration. Theory suggests that women's sexuality is contextually based. Thus, the understudied intersection of bisexuality and other cultural identities becomes important to examine. Interviews with 14 ethnic minority bisexual women were conducted to investigate factors influencing bisexual identity development and its intersections with cultural identities. Consensual qualitative research re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…After interviewing fourteen ethnic minority, bisexual, cisgender women, Brooks et al (2008) also suggest that stress may be related to the conflict between these women’s bisexual identity and their ethnic culture’s expectations of gender roles. Body surveillance may also be due to the eroticization of bisexual cisgender women in society and fears of being discriminated against due to the stigma (Brooks et al, 2008). Another interpretation is that this study’s participants may have developed more coping strategies and/or protective factors due to their alliance with their racial/ethnic community, potentially buffering the adverse effects of internalized racism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After interviewing fourteen ethnic minority, bisexual, cisgender women, Brooks et al (2008) also suggest that stress may be related to the conflict between these women’s bisexual identity and their ethnic culture’s expectations of gender roles. Body surveillance may also be due to the eroticization of bisexual cisgender women in society and fears of being discriminated against due to the stigma (Brooks et al, 2008). Another interpretation is that this study’s participants may have developed more coping strategies and/or protective factors due to their alliance with their racial/ethnic community, potentially buffering the adverse effects of internalized racism.…”
Section: Discussionmentioning
confidence: 97%
“…This proposes that, due to race and ethnicity being visible constructs of identity, participants may be more likely to maintain a connection with their heteronormative racial/ethnic community than the predominantly White LGBTQþ community (DeBlaere et al, 2014). After interviewing fourteen ethnic minority, bisexual, cisgender women, Brooks et al (2008) also suggest that stress may be related to the conflict between these women's bisexual identity and their ethnic culture's expectations of gender roles. Body surveillance may also be due to the eroticization of bisexual cisgender women in society and fears of being discriminated against due to the stigma (Brooks et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the strains of identifying as both bisexual and as a person of color, their behavior is regulated by the Madonna/whore dichotomy (Klesse, 2005), and for this reason, they may be in even greater need of recognition in research. In a qualitative study by Brooks et al (2008), bisexual racial/ethnic minority women reported their experiences being exotisized because of these two identities, as well as the challenges they face in defying their cultural sexuality and gender role norms. These participants discussed the difficulties they face in their intimate relationships because their bisexual identities may challenge the masculine ideals of the racialized men they date and bemuse the White men they date, due to a lack of common experience and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…These participants discussed the difficulties they face in their intimate relationships because their bisexual identities may challenge the masculine ideals of the racialized men they date and bemuse the White men they date, due to a lack of common experience and understanding. Bisexual women of color are also at increased risk of isolation and poor mental health as they are often alienated from both the LGBTQϩ community and their racial/ ethnic communities (Brooks et al, 2008). This isolation may prevent them from receiving the moderating effects of social support on the relationship between minority stress and poor mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation